2020
DOI: 10.1016/j.freeradbiomed.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Intra-dimer cooperativity between the active site cysteines during the oxidation of peroxiredoxin 2

Abstract: Peroxiredoxin 2 (Prdx2) and other typical 2-Cys Prdxs function as homodimers in which hydrogen peroxide oxidizes each active site cysteine to a sulfenic acid which then condenses with the resolving cysteine on the alternate chain. Previous kinetic studies have considered both sites as equally reactive. Here we have studied Prdx2 using a combination of non-reducing SDS-PAGE to separate reduced monomers and dimers with one and two disulfide bonds, and stopped flow analysis of tryptophan fluorescence, to investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…8 D) concentrations gave a second-order rate constant of 2.3 ± 0.09 × 10 6 and 1.5 ± 0.07 × 10 8 M −1 s −1 , respectively. These values are much in agreement with those calculated by the reaction of urate hydroperoxide with human 2-Cys Prx2 [ 49 ] and by H 2 O 2 with human 2-Cys Prx2 and AhpC from Salmonella typhimurium [ 50 , [63] , [64] , [65] ]. AhpC also seems to react faster with HOCl, however, we could not determine the rate constant by fluorescence since HOCl also oxidizes the tryptophan residues altering protein fluorescence (data not shown).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…8 D) concentrations gave a second-order rate constant of 2.3 ± 0.09 × 10 6 and 1.5 ± 0.07 × 10 8 M −1 s −1 , respectively. These values are much in agreement with those calculated by the reaction of urate hydroperoxide with human 2-Cys Prx2 [ 49 ] and by H 2 O 2 with human 2-Cys Prx2 and AhpC from Salmonella typhimurium [ 50 , [63] , [64] , [65] ]. AhpC also seems to react faster with HOCl, however, we could not determine the rate constant by fluorescence since HOCl also oxidizes the tryptophan residues altering protein fluorescence (data not shown).…”
Section: Resultssupporting
confidence: 87%
“…AhpC rapidly reduces urate hydroperoxide and H 2 O 2 . The rate constants obtained in this study were much similar to that found for the reduction of urate hydroperoxide and H 2 O 2 by the human 2-Cys peroxiredoxin Prx2 and the Salmonella typhimurium AhpC [ 49 , 50 , 64 , 65 ]. We could not calculate the rate constant for the reaction of AhpC with HOCl since the latter also oxidizes tryptophan, interfering in the intrinsic protein fluorescence.…”
Section: Discussionsupporting
confidence: 81%
“…With a 2-fold excess of H 2 O 2 recovery was slower for C172S than for the WT (Fig. 2B), but as expected for hyperoxidation and described in detail in (17), the rate increased with increasing H 2 O 2 concentration. In contrast, the C172D (Fig.…”
supporting
confidence: 70%
“…2A). This recovery is associated with disulfide formation, plus at higher H 2 O 2 concentrations, hyperoxidation (16,17). The C R mutants cannot form disulfides, and the recovery phase is not expected unless there is hyperoxidation.…”
mentioning
confidence: 99%
“…the concentrations tested only trans-WOOH gave rise to hyperoxidized Prx2. It is not clear whether this can be explained simply by the different extent of oxidation, or whether it supports a mechanism of intra-dimer cooperativity, whereby the oxidation by trans-but not cis-WOOH of the first peroxidatic thiol to sulfenic acid in the Prx2 homodimer enhances the rate of oxidation of the second peroxidatic site 58 .…”
Section: Andmentioning
confidence: 99%